2017
DOI: 10.1002/cncr.30924
|View full text |Cite
|
Sign up to set email alerts
|

The association between patient attitudes and values and the strength of consideration for contralateral prophylactic mastectomy in a population‐based sample of breast cancer patients

Abstract: Background Little is known about how the individual decision styles and values of breast cancer patients at the time of treatment decision making are associated with consideration of different treatment options, specifically with consideration of contralateral prophylactic mastectomy (CPM). Methods We identified newly diagnosed patients with early-stage breast cancer treated in 2013–14, identified through SEER registries of Los Angeles & Georgia, and surveyed them about 7 months after surgery (N=2578, RR=71%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
22
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 26 publications
(61 reference statements)
0
22
0
Order By: Relevance
“…The socio‐demographic, clinical, and psychological contributors to CPM have been well established, and prior research has also highlighted the relationship between patient‐driven decision making and CPM . As breast cancer treatment can profoundly impact quality of life, understanding how and why young women make certain decisions about surgery, including undergoing CPM, can have important implications.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The socio‐demographic, clinical, and psychological contributors to CPM have been well established, and prior research has also highlighted the relationship between patient‐driven decision making and CPM . As breast cancer treatment can profoundly impact quality of life, understanding how and why young women make certain decisions about surgery, including undergoing CPM, can have important implications.…”
Section: Introductionmentioning
confidence: 99%
“…5While CPM reduces the risk of developing a contralateral breast cancer, for most women (eg, those without a BRCA1 or BRCA2 mutation), this risk is relatively low, with the 5-year risk estimated to be <5%.Furthermore, there is no evidence that CPM improves survival 2,3 ; thus, this procedure is of limited medical benefit for most women.The socio-demographic, clinical, and psychological contributors to CPM have been well established, 6-8 and prior research has also highlighted the relationship between patient-driven decision making and CPM. 5,9,10 As breast cancer treatment can profoundly impact quality of life, understanding how and why young women make certain decisions about surgery, including undergoing CPM, can have important implications. Young breast cancer survivors often contend with unique issues due to their life stage, including fertility, breastfeeding, and caring for young children, when making these choices.…”
mentioning
confidence: 99%
“…Despite these findings, rates of CPM continue to increase 12,13,21‐25 . Although the reasons for this trend are under investigation, 2,5,7,21,22,26‐28 patient anxiety and overestimation of personal contralateral breast cancer risk (CBC) have received substantial attention as a driving force for the increasing utilization of CPM 4,15,21,24,27,29 . Using patient‐directed surveys, one previous study has shown that patients overestimate their risk for CBC, with 10‐year self‐reported risk estimates over 30% 29 .…”
Section: Discussionmentioning
confidence: 99%
“…[13][14][15][16][17] In addition, many women see surgery choices as their own, especially women with dependent children, 18 and considering prophylactic mastectomy is associated with preferences to make one's own treatment decisions. 19 Women's increasing sense of ownership in surgical decision making and a desire to regain a sense of control could be factors in recent trends toward more frequent prophylactic mastectomies. [20][21][22] A limitation of our study is the use of a proxy parental status measure, although our sensitivity analysis suggested that our measure had good sensitivity and specificity.…”
Section: Discussionmentioning
confidence: 99%